Associations between vigorous physical activity and chronic diseases in older adults: a study in 13 European countries. (14th May 2018) - Marques, Adilson; Peralta, Miguel; Sarmento, Hugo; Martins, João; González Valeiro, Miguel
Abstract: Background: This study aimed to assess cross-sectional and prospective relationships between vigorous physical activity (VPA) and the risk of major chronic diseases among European older adults. Methods: Participants were 37 524 older adults who responded to the fourth (in 2011) and fifth (in 2013) wave of the SHARE project, from 13 European countries. Participants answered interview questions about the presence of chronic conditions and VPA. The cross-sectional and prospective association between PA and the number of chronic diseases was assessed using logistic regression models. Results: Among men and women, the prevalence of chronic diseases was significantly lower among those who reported VPA once a week or more than once a week. For men, VPA once a week was prospectively related with lower odds of heart attack, chronic lung disease, Parkinson's disease and Alzheimer's disease. VPA more than once a week was prospectively related with lower odds of having all chronic diseases. Women who engaged in VPA once a week presented lower odds of having chronic diseases, except for hypertension, high blood cholesterol and cancer. For VPA more than once a week, cancer was the only disease not associated with physical activity. Conclusion: VPA is associated with reduced risk of chronic diseases in men and women. Even the practice of VPA once a week seems to be sufficient to reduce risks of chronic diseases.